PEMERIKSAAN REFRAKSI BAGI PENDERITA KATARAK DI JAYA OPTICAL PADANG - D.I Suryanta (Ensiklopedia of Journal, 2020)
Cataract is a disease that has not found a cure. Cataract is the loss of transparency from the focusing lens in the lens or crystalline eye which is located just behind the colored iris and can only be seen through the pupil. Cataracts, which are the main cause of reduced vision in the world, are estimated to have reached 17 million people with cataract blindness in the world today and will increase to 40 million in 2020. The purpose of this study is (1) to determine the obstacles encountered in refractive examination in cataract sufferers. at Optik Karunia PasarRaya Padang., (2) to find out how to check refraction in cataract patients in Jaya Optical. The type of research used is descriptive quantitative, the research process is carried out through interviews by distributing questionnaires, this study aims to obtain an overview of the refractive examination for optical cataract sufferers in Jaya. The population in this study were all cataract patients who wore glasses. Considering the population under study was less than 100 people, the sample in this study were all cataract sufferers who wore glasses totaling 30 people. The research was conducted on patients suffering from cataracts in Jaya optical. The results showed that the respondents that 30 respondents (100%) felt problems in the refractive examination, that as many as 30 respondents (100%) felt easily dazzled by light, 30 respondents (100%) felt chaotic vision at night, 17 respondents (56 , 7%) felt good refraction examination in cataract patients and as many as 13 respondents (43.3%) stated that they did not feel good refraction examination in cataract patients at Jaya Optical, 22 respondents (73.3%) were asked about eye health and as many as 8 respondents (26.7%) said they were not asked about eye health and 30 respondents (100%) stated that their eyesight was better after being given glasses. Based on the results of this study, it was concluded that 30 respondents (100%) who felt constraints on the refractive examination, 17 respondents (56.7%) felt good refraction examination in cataract patients and as many as 13 respondents (43.3%) stated that they did not feel the refractive examination. which is good for cataract sufferers at Optik Karunia Pasar Raya. This also illustrates that there is a need for evaluation in terms of service to patients, in order to improve the quality and effectiveness of services provided to patients.